A novel ratiometric and turn-on fluorescent coumarin-based probe for Fe(iii). (12th July 2019) - Pivetta, Tiziana; Masuri, Sebastiano; Cabiddu, Maria Grazia; Caltagirone, Claudia; Pintus, Anna; Massa, Michela; Isaia, Francesco; Cadoni, Enzo
Abstract : 6-Methoxy-3-(pyridin-2-yl)-2 H -chromen-2-one exhibited fluorescence enhancement in the presence of Fe(iii ). This molecule was a selective fluorescent chemosensor for Fe(iii ). Abstract : Five coumarin derivatives, able to coordinate Fe(iii ) and exhibit a ratiometric and turn-on fluorescence response, were prepared and tested. The derivative with the –OCH3 substituent exhibited a high fluorescence enhancement in the presence of Fe(iii ), Ga(iii ), Au(iii ) and Y(iii ). Thanks to the higher stability of the Fe(iii ) complexes, this molecule could be proposed as a selective fluorescent sensor for the detection of Fe(iii ) in CH3 CN and CH3 CN : H2 O (1 : 1, v/v) solutions, showing a linear response up to 35.0 μM Fe(iii ) concentration and a limit of detection of 2.4 μM Fe(iii ) concentration. The fluorescence response towards this ion was also tested on a solid surface with a simple cellulose paper-strip test. The peculiarity of the proposed sensor lies in its easy and low-cost synthesis, relevant ratiometric response and, since it is derived from a natural product, low impact on the environment and its organisms.